O sangue na obra de arte: como imagem, como meio de expressão e suas implicações no fazer artístico - Queiroz, Antonio Xavier de (2010)
This research is an invitation to the act of looking, or, in other words, to an intimate "action" towards such a different organic element called Blood, which can be either represented, or materialistically presented as a significant vehicle in the artwork at different times of Art History. Such evolution of Blood as a sthetic material will be done by analyzing the works of different artists such as: Pietro Lorenzetti, Mathias Grünewald, Annibale Carracci, Caravaggio, Artemisia Gentileschi, Francisco Goya, Pedro Américo, Gustave Moreau Frida Kahlo and Candido Portinari. Hermann Nitsch, Ana Mendieta, Gina Pane, Chris Burden, Artur Barrio, Karin Lambrecht, Marc Quinn, Betina Sor, Vanessa Tiegs e Regina José Galindo are contemporary artists, most of them representative either of the so called Body Art or of other innovative styles born after the Second World War or of Vietnam War or after 1968 movements. Anyway, all of them have blood as a fundamental and meaningful element, and this is what will be focused in this work.